Clinical practice and outcomes of palliative radiation therapy in pediatric oncology patients: An international comparison of experiences from two distinct countries and health care systems. (November 2019) - Rao, Avani Dholakia; Figueiredo, Maria Luisa S.; Yegya-Raman, Nikhil; Sehgal, Shuchi; Chen, Qinyu; Alcorn, Sara R.; Chen, Michael J.; Ladra, Matthew; Villar, Rosangela; Terezakis, Stephanie A.
Highlights: This series reviews the clinical indications, toxicity, and outcomes for children treated with palliative RT in distinct practicing environments. Palliative RT cases of pediatric oncology patients in two Brazil-based and one US-based academic centers were reviewed. Sixty-seven percent of patients experienced a complete (CR) or partial response (PR) to palliative RT, 12% reported stable symptoms (SS), and 22% reported progressive symptoms (PS). Clinical results in the two unique healthcare settings demonstrated its success across systems, with some differences in clinical practice patterns. Abstract: Background and purpose: This study describes clinical outcomes of palliative radiation therapy (RT) for children treated in distinct health-care environments—the US where there is advanced integration of palliative resources and Brazil, a country in the process of developing provisions for pediatric palliative care. Methods and materials: Palliative RT cases of pediatric oncology patients aged ≤21-years from 2010 to 2016 in two Brazil-based and one US-based (Johns Hopkins Hospital, JHH) academic centers were reviewed in this study. Results: Eighty-eight pediatric patients were treated to 131 lesions with palliative RT. Forty-nine patients from the JHH cohort comprised 84 cases and 39 patients from the Brazil cohort comprised 46 cases. The most common indication for palliative RT was pain (55% overall, 39% Brazil, 63% JHH). Sixty-seven percent of patients experienced a complete (CR) or partial response (PR) to palliative RT, 12% reported stable symptoms (SS), and 22% reported progressive symptoms (PS). The median survival from the end of palliative RT was 3.6 months (95% confidence interval (CI), 2.3–4.8 months). When treated with palliative RT for pain, 83% of patients experience CR/PR, facilitating reduction or discontinuation of opiates in 46% of these patients. Conclusion: Despite different practices, the clinical results using palliative RT for pediatric patients treated in two unique healthcare environments demonstrated it is an effective tool for pediatric oncology patients across systems.